Clinical Outcome of a Novel Anti-CD6 Biologic Itolizumab in Patients of Psoriasis with Comorbid Conditions - Vinay Singh (Dermatology Research and Practice)
Psoriasis is a common, chronic, immune mediated, inflammatory disease of skin characterized by red patches enclosed with white scales and affects 2-3% of people in the world. Topical therapy, phototherapy, and systemic therapy were employed for management of disease from many last decades. However, long term uses of these agents are associated with unwanted effects and toxicities. Recently, Itolizumab has been developed as world’s first anti-CD6 humanized monoclonal IgG1 antibody for the management of moderate-to-severe chronic plaque psoriasis in India. Here we are presenting the response indicated by Itolizumab in 7 Indian patients having moderate-to-severe psoriasis with severe comorbidities and who were intolerant/nonresponding to conventional therapies.